Analisis Wacana Kritis Sosial Dalam Lagu “Surat Buat Wakil Rakyat Karya Iwan Fals” - Dinda Juwita; Aliasan .; Jufrizal . (CV. ITTC INDONESIA, 2026)
Using a Critical Discourse Analysis (CDA) approach, this study will investigate the social criticism discourse found in Iwan Fals' song